Prevalence of Bullying and Perceived Social Support Among Students in Peshawar - Waleed Ahmad; Muhammad Saqib Siddique; Ruqqia Jahangir; Rabia Rahim (Gandhara University, 2020)
OBJECTIVES: This study aimed to investigate the prevalence of bullying and perceived social support among students in Peshawar, Pakistan. METHODOLOGY: It was a cross-sectional descriptive survey, conducted in different private and government sector schools, colleges and universities of Peshawar (November2019-February 2020). A total of 1000 students participated in the study. We employed a  stratified sampling technique and selected a proportion of students from every academic year. Female students aged 15-24 were included in the study. Informed consent was taken from the students and the concerned authorities of the institutes. A questionnaire was designed to assess the prevalence of bullying behavior and the availability of perceived social support. Pre-testing of the questionnaire was performed on 10% of the population. The obtained data were analyzed in SPSS version 21. RESULTS: The prevalence of bullying was more in university students as compared to college and school students. Similarly, most of the private sector students were the victims of bullying. Family and friends were highly perceived as social support. CONCLUSION: A multidisciplinary approach involving affected children, their parents, school personnel, media, non-governmental organizations, and security units are required to achieve an effective approach for the prevention of violence targeting children in schools as victims and/or perpetrators.